SPIRALE: balloon-borne experiments, atmospheric compounds measurements, flight of 22 June 2005 - Valery, Catoire (AERIS, 2021)
SPIRALE (SPectromètre Infra Rouge pour l'étude de l'Atmosphère par diodes Laser Embarquées) is a spectrometer with six tuneable diode lasers designed for in situ measurements of chemical trace compounds in the upper troposphere and the stratosphere, up to an altitude of 35 km. To date, all flights have taken place successfully, at various latitudes: Kiruna (Sweden, 67.5°N), Aire-sur-l'Adour (43.4°N), Gap (44.3°N) and Teresina (Brazil, 5.08°S). Vertical profiles of concentrations of about a dozen species (O3, CH4, CO, CO2, N2O, HNO3, NO2, NO, HCl, HOCl, H2O2 and COF2) have been measured with very high vertical resolution, high sensitivity and high precision. This flight is involved in the ENVISAT validatio campaign.